New approaches towards organization of independent work of personnel of the State Border Guard Service of Ukraine (Pedagogy of Higher and Secondary Education, 2012)
Berestetska N. New approaches towards organization of independent work of personnel of the State Border Guard Service of Ukraine.On the basis of theoretical analysis of scientific sources and official documents the organization of independent work of personnel of the State Border Guard Service of Ukraine has been analyzed; new approaches of its effective implementation within the border units have been examined; methodical recommendations concerning its improvement have been offered. The main attention has been drawn towards foreign language learning by the personnel of the State Border Guard Service of Ukraine during independent work and development of individual tasks for borderguards as well.
Keywords: independent work; personnel; State Border Guard Service of Ukraine; individual task